Monitoring System for an Experimental Facility Using GMDH Methodology - Iraci Martinez Pereira; Davi Almeida Moraes (Brazilian Journal of Radiation Sciences, 2021)
This work presents a Monitoring System based on the GMDH - Group Method of Data Handling methodology applied in an Experimental Test Facility. GMDH is a combinatorial multi-layer algorithm in which a network of layers and nodes is generated using a number of inputs from the data stream being evaluated. The GMDH method is based on an underlying assumption that the data can be modeled by using an approximation of the Volterra Series or Kolmorgorov-Gabor polynomial. The Fault Test Experimental Facility was designed inspired in a PWR nuclear power plant and is composed by elements that correspond to the pressure vessel, steam generator, pumps of the primary and secondary reactor loops. The nuclear reactor core is represented by an electrical heater with different values of power. The experimental plant is fully instrumented with sensors and actuators. The Fault Test Experimental Facility can be operated to generate normal and faulty data. These failures can be added initially with small magnitude, and their magnitude being increasing gradually in a controlled way. The database will interface with the plant supervisory system SCADA (Supervisory Control and Data Acquisition) that provides the data through standard interface.